Implantation of a totally implanted venous device unexpected discovery of left permanent superior vena cava in a patient with sigmoid colon cancer: a case report - Zhu, Shuchen; Dong, Mingyan; Luo, Haiguan; Piao, Yicui; Zhang, Qiaohong; Huang, Lihui; Liu, Zijie (Frontiers in Surgery, 2025)
Persistent left superior vena cava (PLSVC) is an intrathoracic vascular malformation. Sigmoid colon cancer with a left superior vena cava (LSVC) is very rare. Totally implanted venous devices (TIVADs) are commonly used in recurrent chemotherapy for sigmoid colon cancer. We describe a case of unexpected finding of coronary sinus rhythm in intracavitary electrocardiogram localization TIVAD implantation. Intraoperative ultrasonography revealed a PLSVC.